Functional Ability Classification Based on Moderate and Severe Kinesophobia and Demoralization Scores in Degenerative Spine Patients. Issue 15 (1st August 2021) - Haddas, Ram; Lieberman, Isador; Sandu, Cezar D.; Sambhariya, Varun; Block, Andrew
Abstract : Study Design: A prospective cohort study. Objective: To assess the relationship of fear avoidance and demoralization on gait and balance and determine a threshold score for the Tampa Scale for Kinesophobia (TSK) and the Demoralization Scale (DS) that identifies spine patients with gait and balance dysfunction amplified by underlying psychological factors. Summary of Background Data: Fear avoidance and demoralization are crucial components of mental health that impact the outcomes in spine surgery. However, interpreting their effect on patient function remains challenging. Further establishing this correlation and identifying a threshold of severity can aid in identifying patients in whom a portion of their altered gait and balance may be amplified by underlying psychologic distress. Methods: Four hundred five symptomatic spine patients were given the TSK and DS questionnaires. Patient's gait and balance were tested with a human motion capture system. A TSK score of 41 and a DS score of 30 were chosen as thresholds to classify moderate versus severe dysfunction based on literature and statistical analysis. Results: Higher TSK and DS scores were correlated with worse walking speed ( P  < 0.001), longer stride time ( P  = 0.001), decreased stride length ( P  < 0.048), and wider step width (<0.001) during gait as well as increased sway across planes ( P  = 0.001) during standing balance. When classified by TSK scores >41, patients with more severe fear avoidance had slower walking speed ( P  < 0.001), longer stride time ( P  = 0.001), shorter stride length ( P  = 0.004), increased step width ( P  < 0.001), and increased sway ( P  = 0.001) compared with their lower scoring counterparts. Similarly, patients with DS > 30 had slower walking speed ( P  = 0.012), longer stride time ( P  = 0.022), and increased sway ( P  = 0.003) compared with their lower scoring counterparts. Conclusion: This study demonstrates that fear avoidance and demoralization directly correlate with worsening gait and balance. Furthermore, patients with TSK > 41 and DS > 30 have more underlying psychological factors that contribute to significantly worse function compared with lower scoring peers. Understanding this relationship and using these guidelines can help identify and treat patients whose gait dysfunction may be amplified by psychologic distress. Level of Evidence: 3 Abstract : In symptomatic spine patients, elevated levels of fear avoidance and demoralization directly correlate with gait and balance dysfunction. Identifying patients with gait dysfunction amplified by underlying psychological factors can help treat those patients with more appropriately.